Investigating the adequacy of horizontal lifeline system design through case studies from Singapore - Goh, Yang Miang; Wang, Q. (American Society of Civil Engineers (ASCE), 2015)
Horizontal lifeline system (HLLS) is one of the most widely used fall arrest systems for mitigating the risk of work-at-height in the construction and building industry. A HLLS must ensure the maximum arrest load created during a fall arrest does not exceed the capacity of the anchors and other system components. In addition, the maximum arrest force experienced by the user of the HLLS has to be kept below 6 kN (Europe, Australia, and Singapore) or 8 kN (North America). Finally, the height clearance must be sufficient to prevent the user from hitting the ground or obstacles. To achieve these safety criteria, a HLLS should be designed using appropriate calculation methods. This study evaluated 11 HLLS designs in Singapore based on common standards. A comprehensive calculation template was developed based on energy balance method to facilitate the evaluation. It was discovered that all 11 designs were not adequately endorsed or calculated. This is a potentially dangerous situation because HLLSs are usually the last line of defense for falls from height. The study demonstrated the current competency gap in design of HLLSs in Singapore. Engineers in Singapore are not adequately exposed to the concept of fall protection engineering. Thus, many of them tend to underestimate the forces involved in a fall arrest and did not spend sufficient effort to design HLLSs. It is believed that the problem is not unique to Singapore. Four measures were proposed to close this competency gap and promote sharing of best practices internationally. First, specialized training must be provided to engineers designing HLLSs. Second, it was proposed that design guides should be more detailed so as to help engineers understand what is required in a proper design of HLLSs. Third, a case-based reasoning system (CBRS) was proposed to help engineers improve their HLLS design and at the same time accumulate an international repository of HLLS designs. The CBRS will also contain a HLLS design template to facilitate designs of HLLS and other active fall protection systems. Last, it was proposed that manufacturers should make HLLS properties and detailed information on fall arrest equipment more readily available to engineers.